Pengaruh Pemupukan terhadap Pertumbuhan Bibit Garut (Maranta arundinacea L.) di Bawah Naungan 50% - Ninik Setyowati (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
A study on the effect of fertilizer on the growth of arrowroot (Maranta arundinacea L.) seedling under 50% shading was conducted in the Experimental Garden of Research Center for Biology-LIPI, Cibinong. The research was conducted with Factorial patterns in Randomized Completely Block Design with 2 factors and 5 replications. The first treatment was fertilizing with 2 levels of factors i.e. W1 = 1x fertilizing in the early of planting and W2 = 2x fertilizer (the early and 5 month age of seedling). The second treatment was the kinds of fertilizer with 5 levels of factors i.e. P1 = Control (without fertilizer), P2 = manure of goat dunk, P3 = manure of chicken dung, P4 = manure of cow dung, P5 = compost fertilizer. The result showed that two time application of manure of goat dung (P2) is the best for growing the arrowroot seedling (98.6 cm of plant height, 100 sheet of leaf number, and 8 clumps). The lowest data was seen at control with 1 time fertilizing i.e. 39.6 cm of plant height, 28 sheet of leaf number, but the clump is 3.2 more than the compost fertilizer (2.8 of clumps). This treatment was also seen to increase the plant height adding of arrowroot seedling during observation. The frequency of fertilizer was significantly effect the growth of vegetative parts of plant, i.e. 2x fertilizer better than 1x fertilizer.